Rapid Assessment of Canned Fish Quality via Fast Protein and Metabolite Liquid Chromatography - Oksana V. Stepanova; Daniil Lyalin; Oksana S. Stepanova; Georgii Konoplev; Artur I. Kuznetsov; Liubov Abramova; Andrey Kozin; Aleksandr Frorip (Engineering Proceedings)
The consumption of canned fish as an affordable and shelf-stable food product having high nutritional value is steadily growing in many parts of the world. An important and often overlooked factor that influences the quality of canned fish is the freshness of raw materials used in the production process. It has been shown previously that the freshness status of fish can be assessed using fast proteins and metabolite liquid chromatography (FPMLC) detecting the relative content of post-mortem adenosine triphosphate (ATP) metabolites. The aim of this study is to evaluate the applicability of FPMLC to evaluate the quality of canned fish. Eighteen samples of various canned fish from different manufacturers were acquired from local supermarkets. FPMLC chromatograms of the samples were processed with the compact optoelectronic chromatographic sensor using PD-10 gel columns as a separation medium. The sensor has a photometric detector based on a deep UV LED emitting at 255–265 nm. All chromatograms showed two combined peaks: the first one was related to proteins and the second one was formed by adenosine ATP metabolites. The delay time between the peaks (the Time index) varied in a range from 138 s to 193 s. It was suggested that the higher the Time index, the fewer fresh raw fish materials were used for production. For additional verification of the FPMLC technique, four samples chosen as the most representative were analyzed by high-performance liquid chromatography (HPLC) and nuclear magnetic resonance (NMR) spectroscopy. The Time index was in good correlation with the well-established nucleotide-based K and KI indices (quality factors) estimated from the HPLC chromatograms and NMR spectra, which confirms the fact that FPMLC can be used to assess the freshness of raw materials in thermally processed fish products. The correct interpretation of the Time index and other nucleotide-based indicators applied to canned food requires taking into account the effects of nutritional nucleotide thermal degradation that occur during high-temperature sterilization.